Effective epoxy binders and fiberglass for the restoration and strengthening of building structures - Barabash, E.; Danchenko, Yu. (Ways to Improve Construction Efficiency, 2019)
A study of the effectiveness of surfactants and organosilicon substances use to improve the technological properties of epoxy binder, adhesion and strength properties and reduce the residual stresses of cured epoxy polymers in order to create an epoxy binder for the manufacture of the fiberglass. The optimal composition has been developed, which allowed to obtain glass-reinforced materials with high deformation and strength properties.